Practical Django 2 and Channels 2 : building projects and applications with real-time capabilities - Marani, Federico (Apress, 2019)
Learn how to rapidly build your own ecommerce site by applying Django's battle-tested components. This book demonstrates Django's features and conventions to help you develop modern web applications quickly. You'll adopt a "learn by doing" approach and gain a deeper understanding Django by working through a project in which the real-time component will be critical. The book starts with the basics and explains the difference between a Django project and a Django app, the most important settings, how to change them, and the fundamentals of packaging. You'll then be introduced to all the standard tools of Django, along with a sample project. The book then moves on to Channels, a recent addition to the Django ecosystem. It extends the framework with support for real-time operations such as Websockets and other asynchronous features. Practical Django 2 and Channels 2 provides the practical concepts needed to create complex, database-driven websites as easily as possible